The expanding workweek? Understanding trends in long work hours among US men, 1979 - 2004 - Peter Kuhn; Fernando Antonio Lozano (Institute for the Study of Labor (IZA), 2006)
After declining for most of the century, the share of employed American men regularly working more than 50 hours per week began to increase around 1970. This trend has been especially pronounced among highly educated, high-wage, salaried, and older men. Using two decades of CPS data, we rule out a number of factors, including business cycles, changes in observed labor force characteristics, and changes in the level of men's real hourly earnings as primary explanations of this trend. Instead we argue that increases in salaried men's marginal incentives to supply hours beyond 40 accounted for the recent rise. Since these increases were accompanied by a rough constancy in real earnings at 40 hours, they can be interpreted as a compensated wage increase.
Keywords: J22; 330; labor supply; work hours; Arbeitszeit; Überstunden; Angestellte; USA